Music education in the campuses of Tribhuvan University - Regmi, Dhrubesh Chandra (Journal of Fine Arts Campus, 2022)
An organized music education system is pivotal for the overall development of an individual or the country. The country which has a systematic music education creates opportunities for all types of music related professionals.  Many countries have incorporated music into their education system. Sad to say, no governments in the Nepali History ever made effort to establish and to promote a broad-based, organized and institutionalized music education. It is only after 1951, the organized and institutionalized music education have begun to put down roots in Nepal. The establishment of Tribhuvan University (TU) in 1959 can be taken as a momentous event in this regard. In this paper, we take a look at the role of Tribhuvan University and campuses under it contributing to the development of music education in Nepal. This paper tries to portray the current state of music in the campuses under the TU.